ACR Appropriateness Criteria® Hodgkin Lymphoma—Unfavorable Clinical Stage I and II. (August 2016) - Roberts, Kenneth B.; Younes, Anas; Hodgson, David C.; Advani, Ranjana; Dabaja, Bouthaina S.; Dhakal, Sughosh; Flowers, Christopher R.; Ha, Chul S.; Hoppe, Bradford S.; Mendenhall, Nancy P.; Metzger, Monika L.; Plastaras, John P.; et al.
Abstract : These guidelines review the historical evolution of treatment for early-stage Hodgkin lymphoma (HL) with current standards that rely on prognostic factors to risk stratify and direct current treatment schemes that includes differentiation of favorable and unfavorable presentations. The major clinical trials for unfavorable early-stage HL are reviewed. Patients in this heterogenous subgroup of classic HL are best managed with sequential chemotherapy and radiotherapy. The role of imaging response assessment as a means to modify therapy is a strategy under investigation. Tailoring the radiation treatment volume and radiation dose prescription along with selective use of modern conformal techniques is expected to help reduce long-term toxicities. Many patients are well served receiving involved-site radiotherapy to 30 Gy after appropriate systemic therapy intensity; but, there are nuances for which some variations in the chemotherapy and radiotherapy specifics are appropriately individualized. Following a discussion of the current evidence-based treatment algorithms, several different example cases are reviewed to help physicians make appropriate treatment decisions. The American College of Radiology Appropriateness Criteria are evidence-based guidelines for specific clinical conditions that are reviewed every 3 years by a multidisciplinary expert panel. The guideline development and review include an extensive analysis of current medical literature from peer-reviewed journals and the application of a well-established consensus methodology (modified Delphi) to rate the appropriateness of imaging and treatment procedures by the panel. In those instances where evidence is lacking or not definitive, expert opinion may be used to recommend imaging or treatment.